The Challenges of the Indonesian Government in Eliminating Gender Bias Practices: The Perspective of Kinship Systems in Indigenous Peoples and Regulations - Rodes Ober Adi Guna Pardosi; Ahmad Fathony (Badan Strategi Kebijakan Hukum, 2022)
Gender bias is a condition that indicates the existence of a preference for one of the socially and culturally constructed traits inherent in men and women. Gender differences in treatment harm certain genders. The losses mentioned are related to family and social status contexts. This paper is a normative study using a normative-legal approach, focusing on legal discrimination and observing gender practices in regulation through indigenous kinship systems and literature research. This paper aims to examine gender bias practices, and government efforts to prevent and overcome gender bias practices in Indonesia. Sexist practices are found in Indigenous peoples' lives, regulations, and government policies. Government efforts to prevent and control include ratification of international regulations and ratification in the form of legal instruments. However, other measures are needed from a prevention perspective such as: Political involvement of governments in socialization in the form of an improved understanding of indigenous peoples, the revision of rules that may lead to